Study of the genetic polymorphism of diploid wheat Triticum boeoticum Boiss. using SSR markers - M. A. Abbasov (Вавиловский журнал генетики и селекции)
Diploid wheat Triticum boeoticum Boiss. (genome constitution AA) is a promising source of new valuable alleles for improving cultivated wheat species. Therefore, the evaluation of the intraspecies diversity of T. boeoticum and DNA fingerprinting of accessions of this species are topical tasks. In this paper, the genetic diversity of over 60 T. boeoticum accessions was studied using 11 SSR markers. The analysis revealed 83 alleles, 7.5 alleles per locus on the average. The values of expected (HE) and observed (HO) heterozygosity varied within 0.00–0.74 and 0.17–0.89, respectively, the average indices being HO = 0.13 and HE = 0.52. The PIC value for each locus was within 0.17–0.88, 0.49 on the average. Unique alleles were found in all loci studied. Cluster analysis allowed the accessions studied to be combined into five major groups. The distances between the groups varied from 0 to 1, pointing to a high level of genetic differences in the collection under study. On the base of PCoA, five major groups were formed and some correspondence with the dendrogram was detected. Summarizing the data of PCoA and cluster analysis, we noted a weak genetic differentiation in the studied collection of T. boeoticum. A correlation between the genetic distance and geographic origin was revealed only for accessions of diploid wheat T. boeoticum from Iran. The analysis of the T. boeoticum accessions studied showed a wide diversity for SSR loci. The results expand our knowledge and provide additional information on the genetic structure of the collection and on the genetic diversity of T. boeoticum accessions studied.